2022
DOI: 10.1002/ajoc.202100704
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Catalyst Reduction Temperature on Autogenous Glycerol Hydrogenolysis over NiAl Catalyst

Abstract: Autogenous glycerol hydrogenolysis to 1,2-propanediol by aqueous phase reforming (APR) was investigated over supported nickel catalysts. Effect of reduction temperature on physico-chemical properties of catalysts played a significant role in tuning conversion and product selectivities. The formation of nickel aluminate (NiAl 2 O 4 ) spinel phase during catalyst reduction led to rearrangement of Ni species to obtain small and stable Ni particles. The catalyst activation temperature alters the extent of reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…The catalyst characterization data revealed that the formation of NiAl 2 O 4 spinel phase, smaller nickel particles ( < 8 nm), presence of moderate acid sites and the optimal B L −1 ratio of 1.35 are the key factors for the high catalytic performance. 202…”
Section: In Situ Glycerol Hydrogenolysismentioning
confidence: 99%
“…The catalyst characterization data revealed that the formation of NiAl 2 O 4 spinel phase, smaller nickel particles ( < 8 nm), presence of moderate acid sites and the optimal B L −1 ratio of 1.35 are the key factors for the high catalytic performance. 202…”
Section: In Situ Glycerol Hydrogenolysismentioning
confidence: 99%